TI_GERICHTE 35.2021.5 vom 18. Mai 2021 , Nessun diritto a rendita e IMI del 15%. DSO confermata. Deduzione sociale del 5% confermata - TI Tribunale d'appello (2021)
Nessun diritto a rendita e IMI del 15%. DSO confermata. Deduzione sociale del 5% confermata